Cytomegalovirus infection after kidney transplantation: real progress and prospects for pathogenesis research, prevention and treatment - E. I. Prokopenko (Вестник трансплантологии и искусственных органов)
Cytomegalovirus (CMV) infection plays an important role in clinical transplantology – it increases the risk of complications, graft failure, and patient death. The virus has both direct (direct damage to organs and tissues) and indirect immunomodulatory effects. Based on studies conducted, an international group of experts developed general principles for managing CMV infection after transplantation. This paper discusses risk factors, pathogenetic mechanisms by which CMV infection develops after kidney transplantation, the principles of diagnosis, treatment and prevention of this complication, and ways to overcome drug resistance in the virus. The prospects for the use of immunological monitoring, new antiviral drugs, as well as the possibility of using CMV vaccines, T-cell therapy, immunosuppressants (antiviral mTOR inhibitors) are discussed.